FRONT-END SECURITY ARCHITECTURE: PROTECTION OF USER DATA AND PRIVACY - Chechet, A. S.; Chernykh, M. V.; Panasiuk, Ia. S.; Abdullin, I. I. (Systems and Technologies, 2024)
Investigation of this topic is relevant in light of the significant increase in the frequency and scale of cyber-attacks that affect various industries and organisations. The purpose of this study is to analyse existing data protection methods at the Front-end, which are able to effectively protect the confidentiality of user data in the face of modern cyber threats. Among the methods used, the analytical method, synthesis, classification, statistical and other methods should be noted. The study identified serious risks associated with storing confidential data on the client side. In particular, the use of cookies and local storage turned out to be vulnerable points that pose potential threats to data security. An analysis of existing web applications revealed the presence of cross-site scripting (XSS) vulnerabilities, which became a route for the introduction of malicious scripts. It was revealed that the generation and use of unique cross-site request forgery (CSRF) tokens for each request play a key role in preventing cross-site request forgery. The implementation of Governance as Code (GaC) technology has demonstrated potential for automating compliance with established architectural and security standards, thereby reinforcing front-end defenses against cyber threats. The findings emphasise the importance of educating end users on the basic principles of network security. The study highlights the importance of developers’ active involvement in Front-end security. Thus, a comprehensive overview of the Front-end security architecture with a focus on protecting user data and ensuring privacy is provided. The practical significance of the study lies in the provision of specific recommendations and practical solutions to improve Front-end security in web applications and represents a valuable set of tools and approaches that can be applied by developers and engineers to strengthen the security of web applications. The addition of Governance as Code technology introduces an innovative layer of automated security enforcement that is particularly suited to addressing emerging cybersecurity challenges in real-time.